The constructive approach of the audit on management by results of public universities - Luciano-Villar, Linver (2019)
The investigation purpose was to describe the aptitudes, attitudes and constructive behaviors that the auditor assumes when formulating and implementing an audit program addressed to the effective and efficient use of the resources of public universities, searching the optimization of its management by results. The study type was qualitative, in the Applied level of non-experimental design; the descriptive method was used, according to the period of execution: transverse of correlational descriptive type; according to the purpose of the investigation it was applied to a stratified probabilistic sample of 332 people who take part of the organ of government, permanent professors and office workers of public universities who are part of the Consortium of Universities of the Center of the Peru. Integrated by the national universities: Hermilio Valdizan of Huánuco, of Centro de Huancayo, Daniel Alcides Carrión of Cerro de Pasco and of Huancavelica. The instrument was the survey where the technique of the questionnaire was used which was applied to the analysis unit. The data were processed using of the statistical inference; the hypothesis testing was performed using the non- parametric statistical of the chi – square test. It is concluded that, of the results achieved: it is evidenced that the 2988 data extracted, 97.72% (2920) confirms that there is a positive incidence of the constructive approach of the audit based on the aptitude, attitude and behavior of the auditor in the determination of the efficient use of the resources, effective and optimum management by results of public universities. While 2.28% (68) shows that there is not any degree of incidence doesn't exist.